Peran Mediasi Customer Relationship Management: Hubungan Antara Social Media Marketing Terhadap Brand Awareness (Studi Pada Produk Fashion “This Is April” di Kota Malang). - Rahmi, Siti Rafika; Hidayati, Nur; Normaladewi, Andi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research is motivated by the rapid growth of the fashion industry driven by technological advances and digitalization, especially through social media as the main marketing platform. This study aims to examine how Customer Relationship Management (CRM) can mediate the impact of Social Media Marketing (SMM) in increasing Brand Awareness. The sample in this study was 100 respondents. The data collection technique in this study used a questionnaire from respondents who used the product